APPLICATION OF CYBER NOTARY IN THE POSITION OF NOTARY IN INDONESIA - Irwan Santoso (Universitas Labuhanbatu, 2024)
A notary is a public official who is given the authority to make authentic deeds. In making authentic deeds, basically they still have to be made using conventional concepts as regulated in Article 1868 of the Civil Code. As technology develops, conventional methods are felt to hinder economic development, so opinions arise that cyber notary can be implemented. The aim of this research is to find out how cyber notary is implemented in Indonesia. The approach method used in this research is normative juridical using utilitarian theory with the concept of benefit and the lex superior derogate legi inferior theory. The results of this research are that the new cyber notary concept can be applied in making deeds for General Meetings of Shareholders of Limited Liability Companies as regulated in the Company Law and notary protocols in this case are still kept conventionally so changes are needed to the law on notary positions.Keywords: Cyber Notary; Information and Technology; Notary Public Position Act.